Comparative Analysis of the Measles Antibody Levels in Healthy Medical Personnel of Maternity Ward and Women in Labor - Kostinov, Mikhail Petrovich; Zhuravlev, Pavel Ivanovich; Gladkova, Lylia Solomonovna; Mashilov, Kirill Vadimovich; Polishchuk, Valentina Borisovna; Shmitko, Anna Dmitrievna; Zorina, Veronika Nikolaevna; Blagovidov, Dmitriy Alexeyevich; Pahomov, Dmitriy Vladimirovich; Vlasenko, Anna Egorovna; Ryzhov, Alexey Anatolevich; Khromova, Ekaterina Alexandrovna (Frontiers in Immunology, 2021)
It has been proven that post-vaccination immunity to measles virus after 2 doses of vaccine is not able to persistently protect against infection throughout life. The aim of the study is to determine the immune layer to the measles virus among women in labor and maternity ward personnel in the same medical institution. The levels of IgG antibodies to measles virus in the umbilical cord blood of 594 women in labor and 88 workers of the maternity ward were studied by ELISA. It was revealed that 22.7% of umbilical cord blood serum samples from parturient women and 21.4% of blood serum samples from maternity ward personnel were seronegative (<0.18 IU/ml). Levels of IgG antibodies to measles virus in low values (< 1.0 IU / ml) were detected in 67% of blood serum samples among women in labor and in 68,9% among employees of the maternity ward. Among women in labor, women under 35 years are at the highest risk of contracting measles, the proportion of women with low levels of protective antibodies in this age group was almost 70%, and the proportion of women without protective levels of antibodies was 23%. Compared with the age group 36-43, the age of women in labor under 35 is associated with a higher chance of not having immune protection against infection with measles virus OR [95% CI] = 2.2 [1.1-4.5] (p = 0 , 02) or have a low level of protection OR [95% CI] = 1.9 [1.2-3.0] (p = 0.001). It was also found that among women over 35 years of age, the proportion of persons with a high level of antibodies in women in labor is statistically significantly higher than among members of the maternity ward staff (13% and 0%, respectively, p = 0.007). Maternity ward employees and women in labor constitute a risk group for measles due to the presence of a high proportion of seronegative persons among women of childbearing age (both maternity ward employees and women in labor). These conditions create the need to revise current approaches to present vaccination procedures, especially in current epidemiological situation with COVID-19.